2018
DOI: 10.21147/j.issn.1000-9604.2018.02.06
|View full text |Cite
|
Sign up to set email alerts
|

A multicenter hospital-based diagnosis study of automated breast ultrasound system in detecting breast cancer among Chinese women

Abstract: We observed a good diagnostic reliability for the ABUS. Considering its performance for breast cancer detection in women with high-density breasts and its lower operator dependence, the ABUS is a promising option for breast cancer detection in China.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 29 publications
0
17
1
Order By: Relevance
“…We then screened titles and abstracts to exclude 322 articles that did not meet the inclusion criteria or that met the exclusion criteria. We completely evaluated the remaining 82 articles, among which 17 (12 in English, 5 in Chinese) (13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29) were selected for diagnostic accuracy analysis and 13 (11 in English, 2 in Chinese) (22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34) were selected for detection rate analysis (Figure 1). Because 8 articles were used for both diagnostic accuracy and detection rate, a total of 22 articles (13-34) were included in this study (Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…We then screened titles and abstracts to exclude 322 articles that did not meet the inclusion criteria or that met the exclusion criteria. We completely evaluated the remaining 82 articles, among which 17 (12 in English, 5 in Chinese) (13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29) were selected for diagnostic accuracy analysis and 13 (11 in English, 2 in Chinese) (22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34) were selected for detection rate analysis (Figure 1). Because 8 articles were used for both diagnostic accuracy and detection rate, a total of 22 articles (13-34) were included in this study (Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…More recently, Zhang et al [35] demonstrated a better diagnostic performance of ABUS versus HHUS, in particular in the detection of precancerous lesions or cancers (BIRADS 4-5). In this hospital-based multicentre diagnostic study, Zhang et al [35] have evaluated the clinical performance of the ABUS for breast cancer detection by comparing it to handheld ultrasound and mammography (MG) in 1973 women, from 30 to 69 years.…”
Section: Clinical Practicementioning
confidence: 99%
“…More recently, Zhang et al [35] demonstrated a better diagnostic performance of ABUS versus HHUS, in particular in the detection of precancerous lesions or cancers (BIRADS 4-5). In this hospital-based multicentre diagnostic study, Zhang et al [35] have evaluated the clinical performance of the ABUS for breast cancer detection by comparing it to handheld ultrasound and mammography (MG) in 1973 women, from 30 to 69 years. The results not only shown a good diagnostic performance of ABUS but also that the ABUS results, compared to HHUS, were more consistent with the pathology results in the BIRADS 4-5 groups: 78.6% of women classified as BI-RADS 4-5 based on the ABUS were diagnosed with precancerous lesions or cancer, which was 7.2% higher than that of women based on HHUS.…”
Section: Clinical Practicementioning
confidence: 99%
“…Studies have shown that in asymptomatic women with normal mammography but dense breasts ABUS is capable of detecting approximately two breast cancers per 1000 women tested 75 . A multicentric hospital-based cross-sectional study carried out in China in 2016 compared HHUS, ABUS and mammography in 1974 CBE-positive women aged 30-69 years 76 . The results suggest that ABUS has the comparable clinical performance to HHUS for breast cancer detection, and both traditional ultrasound and ABUS have better performance than mammography, especially among women with high-density breasts.…”
Section: Screening For Breast Cancermentioning
confidence: 99%